All Commuting Solutions of a Quadratic Matrix Equation for General Matrices (Journal of Nonlinear Modeling and Analysis, 2024)
Using the Jordan canonical form and the theory of Sylvester'sequation, we find all the commuting solutions of the quadratic matrix equation $AXA = XAX$ for an arbitrary given matrix $A$.